2005
DOI: 10.1007/bf02724406
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of general public and health professionals about tetanus immunization

Abstract: There is a need to upgrade the level of knowledge among health care providers so as to ensure that schedules of tetanus are followed properly and unnecessary repeated immunizations are avoided and the same knowledge is passed on to the general public also.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Another study from Singapore evaluated the knowledge of GPs regarding childhood developmental and behavioral disorders and reported that only 37% of GPs achieved a passing (score of at least 75%) grade (Lian et al 2003). Other studies from South Asia including Pakistan reported that a significant portion of GPs in South Asia lack sufficient knowledge and skills regarding diagnosis or management of common health issues, such as acute respiratory infections or tuberculosis (Ahmed et al 2009;Aziz et al 2006;Dabas et al 2005;Dobe 1995;Kamat 2001;Kumar et al 2006a, b;Patwari et al 1991;Rizvi and Hussain 2001;Roy et al 2005;Shah et al 2003;Shaikh et al 2008;Shehzadi et al 2005;Uddin et al 2008;Vandan et al 2008Vandan et al , 2009. The data presented in this paper support that GPs in Pakistan are lacking important knowledge about autism and perhaps other diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from Singapore evaluated the knowledge of GPs regarding childhood developmental and behavioral disorders and reported that only 37% of GPs achieved a passing (score of at least 75%) grade (Lian et al 2003). Other studies from South Asia including Pakistan reported that a significant portion of GPs in South Asia lack sufficient knowledge and skills regarding diagnosis or management of common health issues, such as acute respiratory infections or tuberculosis (Ahmed et al 2009;Aziz et al 2006;Dabas et al 2005;Dobe 1995;Kamat 2001;Kumar et al 2006a, b;Patwari et al 1991;Rizvi and Hussain 2001;Roy et al 2005;Shah et al 2003;Shaikh et al 2008;Shehzadi et al 2005;Uddin et al 2008;Vandan et al 2008Vandan et al , 2009. The data presented in this paper support that GPs in Pakistan are lacking important knowledge about autism and perhaps other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, no GPs were adequately familiar with associated factors and clinical symptoms of LD (Jawaid et al 2008). Similar studies have assessed the knowledge and skills of GPs in Pakistan and India (Roy et al 2005) regarding common health problems and other disorders including diabetes (Kumar et al 2006a), cancer and palliative care (Shaikh et al 2008), helicobacter pylori infection (Ahmed et al 2009), tuberculosis (Rizvi and Hussain 2001;Shah et al 2003;Shehzadi et al 2005;Vandan et al 2008Vandan et al , 2009, acute respiratory infections (Iqbal et al 1997), acute diarrhea (Patwari et al 1991), malaria (Kamat 2001), sexually transmitted infections (Khandwalla et al 2006), AIDS (Dobe 1995) and preventing tetanus (Dabas et al 2005;Kumar et al 2006b). These studies demonstrate that a high percentage of GPs in Pakistan and India lack sufficient knowledge regarding diagnosis and management of these diseases.…”
mentioning
confidence: 97%
“…It has previously been shown that knowledge about tetanus can be that poor even among healthcare workers in countries with high burden of the disease (21). Though tetanus as a disease may be mentioned in some of the subjects that are taught in schools, it is not clear how much of such information students would be able to recall.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on the vaccinators' theoretical knowledge of vaccinations and vaccination programs, finding that such knowledge varied largely, and, according to many studies, did not always meet the requirements. In particular, contraindications of vaccinations were not clear to vaccinators (Cohen, Lauderdale, Shete, Seal, & Daum, 2003; Dabas et al, 2005; de la Hoz, Perez, Wheeler, de Neira, & Hall, 2005; Harr, Hammar, & St.John‐Seed, 2001; Petousis‐Harris, Goodyear‐Smith, Turner, & Soe, 2004, 2005). Vaccinating has also been examined from the practical point of view, such as injection techniques.…”
mentioning
confidence: 99%
“…Some earlier studies have examined vaccinators' knowledge and the impact of education on vaccination distribution. According to them, vaccinators were in need of constant education (e.g., Dabas et al, 2005; Daly et al, 1992; de la Hoz et al, 2005; Heurter et al, 2003; Mawn & Pakkala, 2000; Petousis‐Harris et al, 2004, 2005), and the need for education in nursing programs and universities has been noted (Swennen et al, 2001). As for pedagogical solutions, researchers have suggested interactive methods and peer discussions (Lewendon et al, 2001).…”
mentioning
confidence: 99%